Release of lysosomal enzymes in Tetrahymena: a Ca²⁺-dependent secretory process - Tiedtke, Arno (1988)
The ciliate Tetrahymena thermophila releases lysosomal enzymes into nutrient and starvation media. We show here that this process occurs selectively, i.e. without leakage of cytoplasmic components, as indicated by lack of release of isocitrate dehydrogenase, a cytosolic enzyme with high activity in Tetrahymena . The role of intracellular Ca²⁺ in the process was also investigated. The Ca²⁺ ionophore A23187 has strong stimulatory effects on this release. Ionophore stimulation is maximal in the presence of extracellular Ca²⁺ but can occur also in its absence. Quin 2 fluorescence measurements indicate that intracellular Ca²⁺ increases in both cases. Mg²⁺ completely prevents the stimulatory effects of A23187. Ionomycin, another Ca²⁺ ionophore, also stimulates lysosomal enzyme release with a maximal response in the presence of extracellular Ca²⁺ . Measurements of extracellular isocitrate dehydrogenase showed that ionophore-stimulated lysosomal enzyme release can take place without leakage of cytoplasmic components. The observations that divalent cation ionophores stimulate selective lysosomal enzyme release and that this effect is strongest in the presence of external Ca²⁺ indicate that this cation plays a crucial role in the control of this process in Tetrahymena . Together with other observations they support the view that a subpopulation of Tetrahymena lysosomes has properties like those of secretory vesicles.